Determinant of catastrophic costs associated with treatment for rifampicin-resistant TB in households in the Republic of Moldova - A. Ciobanu; V. Plesca; S. Doltu; M. Manea; L. Domente; A. Dadu (IJTLD Open)
SETTING: The Republic of Moldova is a lower-middle-income country. Patients with TB face some barriers to accessing TB services. Welfare benefits are available during TB treatment. OBJECTIVES: We aimed to determine the proportion of rifampicin-resistant TB (RR-TB) households that experienced catastrophic costs due to TB at a threshold of ≥20% of household income and investigate the associated risk factors. DESIGN: A cross-sectional countrywide study comprised 430 patients with RR-TB who had received TB treatment as an inpatient or outpatient for at least 2 months. RESULTS: RR-TB patients lost 30% of their household income in inpatient and 70% in outpatient TB care. TB-related costs were associated with being unofficially employed or unemployed (aOR 1.9, 95% CI 1.1–3.3), having fewer household members (aOR 2.1, 95% CI 1.3–3.5), having an income that accounted for over 50% of household income (aOR 2.4, 95% CI 1.5–3.8), and being a poor household (aOR 2.2, 95% CI 1.2–3.9). CONCLUSION: Although TB health services are provided to patients free of charge, 26% of RR-TB households experienced catastrophic TB costs. The associated factors should be considered to improve patient-centred TB care, especially in vulnerable groups. Welfare payments mitigate TB costs.